Pengaruh kastrasi terhadap performan produksi Sapi Persilangan Wagyu berdasarkan umur yang berbeda - Kuswati Kuswati; Ravenska Ravenska; Nareswara Hapsari; Aulia Puspita Anugra Yekti; Trinil Susilawati (Jurnal Ilmu-Ilmu Peternakan (Indonesian Journal of Animal Science), 2016)
The purpose of this research was to know the effect of castration to Wagyu crossbreed cattle production performance based on age difference and know the appropriate age to do castration. The materials used in this research were 37 heads of 3-month old and 28 heads 4 months calf castration. The method was case studies with purposive sampling. Data were analyzed using unpaired t test. The results showed that the calf castration age of 3 months and 4 months showed significantly different (P <0.05) in daily body weight gain and feed conversion. The average daily weight gain of 3 months old calf castration was 0.78 kg / head / day and 4 months old calf castration was 0.85 kg / head / day and feed conversion of 3 months old calf castration was 5.14 and 4 months old calf castration was 4.48, while the feed intake of the research results were not significantly different. The average feed consumption of 3 months old calf castration was 3.82 kg / head / day and 4 months old calf castration was 3.66 kg / head / day. Calves were castrated on 4 months old showed higher daily weight gain than the calf castration on 3 months old. This could be concluded that 4 months old was more appropriate to do castration. Keywords: Average daily gain, calf stock, feed convertion, castration